The effect of conductive fillers and poly (Ethylene Glycol) diglycidyl ether on the properties of poly (Vinyl Chloride)/Poly (Ethylene Oxide) conductive films - Siti Hajar, Mohd Din (Universiti Malaysia Perlis (UniMAP), 2019)
In this research, the conductive films based on poly (vinyl chloride)/poly (ethylene oxide) (PVC/PEO) with conductive fillers like carbon black, polyaniline and polypyrrole were prepared by solution casting method at the speed of 400 rpm. The composition of 5, 10, 15, 20, 25, 30 wt % of filler loading were incorporated in PVC/PEO: 50/50 blends. The tensile properties, morphology, Fourier Transform Infrared spectroscopy (FTIR) analysis, electrical conductivity and thermogravimetric analysis (TGA) were studied. Poly (vinyl chloride)/poly (ethylene oxide)/carbon black (PVC/PEO/CB) at different compositions were prepared. The tensile strength and modulus of elasticity were increased until up to 25 wt% with the addition of the CB by 25.33% and 16.66% respectively. However, at 30 wt% of CB loading, tensile strength and tensile modulus were slightly decreased to 15.87% and 10.7% respectively. The thermal stability and electrical conductivity of PVC/PEO/CB conductive films are increased with the increasing of CB loading. In another system, polyaniline (PAni) filled in PVC/PEO blends explained that the increasing amount of PAni content reduced the 61.24 % of tensile strength and 20.44 % of modulus of elasticity but showed positive increment on electrical conductivity and thermal stability of PVC/PEO/PAni conductive films. The effect of poly (ethylene glycol) diglycidyl ether (PEGDE) on PVC/PEO/CB conductive films decreased 55.65 % of tensile strength and thermal stability but increased 6.45% modulus of elasticity and electrical conductivity. However, addition of PEGDE has increased 1.21% of tensile strength, 6.45% of modulus of elasticity and electrical conductivity but decreased the thermal stability of PVC/PEO/PAni conductive films. The morphology of soaked conductive films indicated that the addition of PEGDE imparted better filler dispersion to the PVC/PEO/CB and PVC/PEO/PAni conductive films. The physical interaction between PVC/PEO blends, PEGDE and conductive filler presented in conductive films was identified by FTIR spectroscopy. In the study, polypyyrole (PPy) filled PVC/PEO conductive films at 15 wt% with the addition of PEGDE exhibited better composition in terms of higher electrical conductivity and thermal stability. However, the tensile strength and modulus of elasticity was lower compared to PVC/PEO/CB and PVC/PEO/PAni conductive films with and without the presence of PEGDE.